THE CODE OF ETHICS OF THE FEDERAL PUBLIC SERVER: PERCEPTIONS AND INFLUENCE ON THE MANAGEMENT OF A PUBLIC UNIVERSITY - Soares Nunes, Thiago; Silveira Santos, Laís (Revista Gestão Organizacional, 2022)
Purpose: describe the perception of professors and technical-administrative staff of an Institution of Higher Education on the practice of the Code of Ethics of the Federal Public Server and its influence in public management. Method / approach: descriptive case study. A quanti-qualitative questionnaire was applied to the staff of the institution studied based on the Code of Professional Ethics of Civil Servant of the Federal Executive Authorities. Main findings: the low use/application of the code of ethics was perceived as a guiding element in institutional actions; the code as a formal system is losing space for other formal systems, such authority structures and systems of reward; but mainly for informal systems, such as the behavior of pairs or unwritten rules. Methodological / social / managerial contributions: the contributions of this paper focus on the debate and administrative reflection of the code of ethics as a guiding system for good practices aimed at the common good, as well as in the construction of moral responsibility for ethical deliberations in the public service. Originality / relevance: a previous study on the code of ethics in public universities indicated that little importance has been given to raising awareness about ethics in the public service. This identification reinforces the need to continue studies on the topic, specifically on its importance and influence on management processes, transparency and good practices aimed at moral action and public interest.